2009
DOI: 10.1089/neu.2008.0657
|View full text |Cite
|
Sign up to set email alerts
|

αII-Spectrin Breakdown Product Cerebrospinal Fluid Exposure Metrics Suggest Differences in Cellular Injury Mechanisms after Severe Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) produces aII-spectrin breakdown products (SBDPs) that are potential biomarkers for TBI. To further understand these biomarkers, the present study examined (1) the exposure and kinetic characteristics of SBDPs in cerebrospinal fluid (CSF) of adults with severe TBI, and (2) the relationship between these exposure and kinetic metrics and severity of injury. This clinical database study analyzed CSF concentrations of 150-, 145-, and 120-kDa SBDPs in 38 severe TBI patients. Area under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
76
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(77 citation statements)
references
References 17 publications
1
76
0
Order By: Relevance
“…Among these, recent studies have suggested that aII-spectrin breakdown products SBDP150 and 145, produced by calpain cleavage, have been linked to acute neuronal necrosis, while SBDP120, produced by caspase 3, has been linked to apoptotic cell death cascades. 41,122,[125][126][127][128][129][130][131] While these aII-spectrin breakdown products have been discussed within the context of neuronal damage, it is important to note that they have been associated with both TAI/DAI and its downstream target deafferentation and synaptic loss. 38,51,[132][133][134] In addition to spectrin breakdown products, other potential markers of axonal injury include various phosphoforms of the neurofilament-H subunit as well as cleaved tau suggesting damage to the axon cytoskeleton.…”
Section: Biomarkersmentioning
confidence: 99%
“…Among these, recent studies have suggested that aII-spectrin breakdown products SBDP150 and 145, produced by calpain cleavage, have been linked to acute neuronal necrosis, while SBDP120, produced by caspase 3, has been linked to apoptotic cell death cascades. 41,122,[125][126][127][128][129][130][131] While these aII-spectrin breakdown products have been discussed within the context of neuronal damage, it is important to note that they have been associated with both TAI/DAI and its downstream target deafferentation and synaptic loss. 38,51,[132][133][134] In addition to spectrin breakdown products, other potential markers of axonal injury include various phosphoforms of the neurofilament-H subunit as well as cleaved tau suggesting damage to the axon cytoskeleton.…”
Section: Biomarkersmentioning
confidence: 99%
“…Examples of these techniques will be taken from studies conducted by our group. In two studies published in the Journal of Neurotrauma in 2007 by Pineda et al 42 and in 2009 by Brophy et al 43 an immunoblotting technique employing sodium dodecyl sulfatepolyacrylamide gel electrophoresis (SDS-PAGE) was used to measure alpha-spectrin. Quantitative evaluation of intact II-spectrin and its breakdown products (SBDP150, SBDP145 and SBDP120) was performed via computer-assisted densitometric scanning.…”
Section: Proteomic Techniques In Neurobiomarker Discoverymentioning
confidence: 99%
“…Western blot analysis of the alpha-II spectrin breakdown products present in a given sample can therefore provide insight into the predominant mechanism of cellular loss . Preliminary studies using alpha-II spectrin breakdown products in humans have demonstrated that necrosis, mediated by calpain, is the predominant mechanism involved in acute DAI, suggesting that calpain inhibitors may be a potential therapeutic target (Brophy et al 2009). …”
Section: Biomarkersmentioning
confidence: 99%